ADVANCES IN MICROBIAL PHYSIOLOGY. (ELSEVIER ACADEMIC PRESS, 2023)
Advances in Microbial Physiology, Volume 150 in this important serial, highlights new advances in the field with this new volume including content by an international board of authors. Chapters in this new release include Organization of respiratory chains in the bacterial cell, Anaerobic methane oxidizing archaea, Dawn of the DedA: the structure and function of the DedA family of integral membrane proteins associated with bacterial viability and antimicrobial resistance, Nickel, an essential virulence determinant of Helicobacter pylori: trafficking pathways and their targeting by bismuth, Dissimilatory sulfur compounds oxidation in thermophilic and chemolithoautotrophic bacteria belonging to the Aquificales order, and much more. Provides the authority and expertise of leading contributors from an international board of authors Presents the latest release in Advances in Microbial Physiology serial.